Aplikasi Pengaduan Sarana dan Prasarana: Studi Kasus di SMK Bhayangkari Delog Berbasis Web dengan Metode Rapid Application Development Menggunakan Sublime Text dan MySQL - Wicaksono, Rizki; Rakryan, Ryan; Faizah, Novianti Madhona (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
With the increasing number of students and the infrastructure supporting educational activities, the complaint service system at SMK Bhayangkari requires improvement. Identified issues include slow response times for feedback, limited flexibility for students to submit complaints, and the manual management of complaint data. This study aims to facilitate students in submitting complaints anytime and anywhere, while simplifying the management of complaint data to expedite the process of checking and following up on complaints. The methodology used in this study is Rapid Application Development (RAD), with system design tools utilizing UML (Unified Modeling Language), PHP programming, and MySQL for the database.